Love, Work, and changes in Extraversion and Neuroticism over Time - SCOLLON, Christie N. (Institutional Knowledge at Singapore Management University, 2006)
The present study examined individual differences in change in extraversion, neuroticism, and work and relationship satisfaction. Of particular interest were the correlations between changes. Data were from the Victorian Quality of Life Panel Study (B. Headey & A. Wearing, 1989, 1992), in which an overall 1,130 individuals participated (ages 16 to 70). Respondents were assessed every 2 years from 1981 to 1989. Four major findings emerged. (a) There were significant individual differences in changes in extraversion and neuroticism. (b) change was not limited to young adulthood. (c) Development was systematic in that increased work and relationship satisfaction was associated with decreases in neuroticism and increases in extraversion over time; on average, the magnitude of the relation between changes in work and relationship satisfaction and traits was .40. (d) Cross-lagged models indicated traits had a greater influence on role satisfaction; however, marginal support emerged for work satisfaction leading to increased extraversion. Implications of correlated change are discussed.